Establish The Perception of Agricultural Extension Workers Through Cyber Extension as The Media Information - Latarus Fangohoi; Sugiyanto Sugiyanto; Keppi Sukesi; Edi Dwi Cahyono (Publisher of Widyagama University of Malang (UWG Press), 2018)
The cyber extension has a significant media in developing an extension program of agricultural information. The government has built the cyber extension supported by the development of ICT and its utilization in the dissemination of agricultural information. It is expected to provide positive benefits in the improvement of competence of the extension workers. The purpose of this research is to analyse the characteristics and perception of the extensions workers in the utilization of cyber extension to support their work. This research is correlational descriptive analysis by using survey method. The study was conducted in South Manokwari Regency, West Papua Province. The sample in the research was all extension workers as many as 22 people. The result shows that the characteristics of the extensions workers as follow: the media used is a smartphone (100 percent), the working period is 5-10 years (77 percent) and the education level is high school (SMK/SPMA, 73 percent). Meanwhile, the perception of the extension workers on the cyber media is high. It reaches 95 percent. They provide the positive perception on cyber extension concerning variables of benefit, complexity, and convenience.JEL Classification: D80, L86, Q16